Culture funding problems in Ukraine in the context of the country’s international commitments: the administrative and legal aspects - Юринець, Юлія Леонідівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
Considered problematic issues of financing culture in Ukraine. The negative impact of insufficient funding of culture in its development. Recalls that, in adopting the Basic Laws of Ukraine on Culture (void of 01.01.2011) was an attempt to ensure adequate funding and logistical support for culture by introducing legislative standard method – at least 8 % of the national income of Ukraine. However, this ratio never followed, and sometimes these rules stop other laws. After the abolition of the Basic Laws of Ukraine about the culture of this standard no longer recovered. Expenditures on culture in the state budget 1991-2004 years. Not exceed 0.33 % of the national income of Ukraine, amounting to 1 % of the consolidated budget expenditures. In the 2005-2013 biennium. Expenditures on culture did not exceed 0.6 % of GDP, amounting to 1.7 % of the total expenditures of the consolidated budget of Ukraine. In an official document – the Law of Ukraine «On the Concept of National Cultural Policy for 2005-2007» (2005) – acknowledged that become a chronic problem of inadequate financial support for the industry of culture. Insufficient funding of culture and/or direct reduction entails reducing the number of social and cultural facilities. It should be noted that the requirements of Ukrainian culture increased funding from the state budget is not a budget support on an exotic culture in Europe. Budgetary funding of culture of European countries is one of the main forms of support to the sector. Expenditures for these needs in the budget range from 0.5 to 4.8 %, which in many cases more than in Ukraine, but with the much larger budgets of these countries in absolute amounts of financing culture in Europe is much more than a Ukrainian realities. Even in Britain, where it is believed there is the smallest state support for culture, state participation in the activities of this culture is from 30 % to 80 %, and the average – 40-50 % of the annual budget organizations culture. It should also be noted that the principles of the cultural policy of the EU and provide guarantees public funding of culture. Thus, the EU resolution Meeting of Ministers of Culture within the framework of the Council of 02.04.1998 on the use of cultural policies for development provides for the need to maintain and increase investment in cultural development at the national level and to provide, where possible, a certain percentage of the government budget for this purpose in accordance with the overall objectives, priorities and programs. It should also be emphasized that if Ukraine, recognizing national culture part of the world (Convention on the Protection of the World Cultural and Natural Heritage, 1972) and European (European Cultural Convention, 1954) Culture and committing to take care of it, does not do so, it is and violation of international obligations of the country. This is not to recognize the justified position of authority about the lack of money in Ukraine shows that Ukraine is actually in public procurement 8 stolen budgets culture. The money for culture is not planned, because on this article cost them more difficult to steal than on public procurement. We conclude that the Europeanization of public administration and administrative law in culture means, in particular, respect for national culture and ensuring proper funding which in Ukraine is not guaranteed.